ESG Disclosure, Market Forces, and Investment Efficiency - Xue, Hao (The Accounting Review, 2025)
ABSTRACT This paper examines the impact of environmental, social, and governance (ESG) disclosure on firm investment. The analysis characterizes the optimal precision of ESG disclosure that channels investors’ tastes for ESG into firm investment. Although it is tempting to think that the optimal ESG disclosure becomes more precise when investors care more about ESG, I show this intuition is incomplete because it overlooks the fact that stronger tastes for ESG change how investors use information. Applying the analysis to a large economy, I show that mandating more precise climate disclosure than would be voluntarily provided motivates self-interested firms to act on common interests in reducing emissions. That is, a regulator can leverage market forces and a disclosure mandate to achieve a similar result as a Pigovian tax in motivating firms to internalize the externalities created by their climate-related investments. JEL Classifications: D82; G14; M41.